In Silico Study of Pretomanid: ADME Evaluation and Molecular Docking for Anti-Tubercular Activity - Komal P. Miskin,; Prabhakar K. Ovhal,; Sandhya P. Kadam, (Asian Journal of Pharmaceutical Research and Development, 2026)
One of the deadliest infectious diseases globally is tuberculosis (TB) due to the appearance of drug-resistant strains of the disease, such as multidrug-resistant (MDR-TB) and extensively drug-resistant (XDR-TB). Pretomaind is a new drug that has become increasingly vital in treating resistant TB and it successfully fights against the deadly bacteria known as 'Mycobacterium tuberculosis'. This essay covers its features, mechanism of action, efficiency, safety and overall importance in the fight against TB. Pretomaind works against the tuberculosis bacteria by inhibiting the building up of its cell walls, as well as releasing toxic compounds to kill all bacteria including those not in their active form. Patients on bedaquiline, linezolid and pretomaind (BPaL) treatment were seen to recover quicker and take less time in studies and have certain limitations such as the tendency to cause liver toxicity, stomach irritation, nerve damage and others that need close monitoring. Overall, pretomaind seems to be a vital addition to combat drug-resistant TB, which will in time further reduce tuberculosis around the world.